A roadmap for cardiovascular care after release from incarceration: uses of a smartphone application. (18th June 2021) - Surkan, Pamela J; Puglisi, Lisa B; Butler, Karim; Elmi, Nika; Zachary, Wayne W
Abstract: Objective: Cardiovascular disease (CVD) and its risk factors disproportionately affect people returning from incarceration. These individuals face multiple barriers to obtaining care, which can impact CVD and risk factor management and may be mitigated through use of a smartphone application (app). Therefore, we explored the CVD-related needs of people released from incarceration and which app features would support these needs. Materials and Methods: In 2019, we collected qualitative data through 7 focus groups with 76 returning citizens and 19 key informants through interviews and small group discussions in Baltimore, Maryland. Verbal data were audio-recorded, transcribed, and analyzed using inductive thematic coding with N-Vivo qualitative software. Results: Returning citizens face multiple barriers when trying to engage in care and services related to cardiovascular health, including around medications and health insurance. Some major challenges were identifying trusted social services and making cardiovascular health a priority. Findings suggested that CVD risk factors could be more effectively addressed in combination with attending to other pressing needs related to employment, housing, behavioral health, and building trust. Participants suggested that a smartphone app would be most useful if it broadly addressed these issues by linking returning citizens to social services, including recommendations from peers, and facilitating access to healthcare. Discussion: Returning citizens need broad support for societal reintegration. Addressing social issues would allow them to focus on cardiovascular health. Conclusion: Given the challenges experienced after release from incarceration, an app focused on social and health-access issues may help returning citizens meet their CVD needs.